Bound on the ratio of decay amplitudes for B̄0 → J/ψK*0 and B0 → J/ψK*0 - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
The time-dependent decay rate for the process B→J/ψK *(892) in γ(4S)→BB̄ decays detected by BABAR detector, was investigated. The flavor-tagged events, where one neutral B meson was reconstructed in the J/ψK*0 or J/ψK̄ *0 final state, were observed. The coefficients of cosine and sine terms in time-dependent asymmetries were also measured. The results show that for a single ratio of wrong-flavor to favored amplitudes for B0 and ̄0 combined, an upper limit of 0.25 at 90% confidence level (C.L.) was obtained.